1996
DOI: 10.1038/eye.1996.139
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy treatment of age-related subfoveal neovascular membranes in patients with good vision

Abstract: This prospective study investigated whether low-dose ionising radiotherapy preserved vision and caused membrane regression in patients with age-related subfoveal neovascular membranes (SFNVMs) or vascularised pigment epithelial detachments (PEDs) and relatively good initial visual acuities. Twenty-five patients with initial Snellen acuities of 6/24 or better were treated with low-dose external beam radiotherapy. Of the patients with SFNVMs, visual acuities were maintained or improved in 58% at 6 months and 53%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
3

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 13 publications
0
10
0
3
Order By: Relevance
“…Obwohl wir diese Studie in keinem kontrollierten Design durchfuhrten, ist der SchluB durchaus zulassig, dal3 sich der Visusverlauf bei unseren Patienten nach Teletherapie nicht wesentlich von dem Spontanverlauf unterscheidet [5]. Ebenso wurde bei keinem Patienten weder fundoskopisch noch angiographisch ein eindeutiger Wachstumstillstand der choroidalen Membranen, wie sie von anderen Autoren beschrieben wurde, beobachtet [6,10]. Nur bei 2 Patienten fiel eine Resorption der serosen Pigmentepithelabhebung auf, das zwar durchaus als Zeichen einer Aktivitatsabnahme gewertet werden konnte, eine Visusverbesserung wurde damit aber nicht erreicht.…”
Section: Diskussionunclassified
See 1 more Smart Citation
“…Obwohl wir diese Studie in keinem kontrollierten Design durchfuhrten, ist der SchluB durchaus zulassig, dal3 sich der Visusverlauf bei unseren Patienten nach Teletherapie nicht wesentlich von dem Spontanverlauf unterscheidet [5]. Ebenso wurde bei keinem Patienten weder fundoskopisch noch angiographisch ein eindeutiger Wachstumstillstand der choroidalen Membranen, wie sie von anderen Autoren beschrieben wurde, beobachtet [6,10]. Nur bei 2 Patienten fiel eine Resorption der serosen Pigmentepithelabhebung auf, das zwar durchaus als Zeichen einer Aktivitatsabnahme gewertet werden konnte, eine Visusverbesserung wurde damit aber nicht erreicht.…”
Section: Diskussionunclassified
“…Die Bestrahlung des hinteren Augenpols mit ionisierenden Strahlen als Therapie der exsudativen altersabhangigen Makuladegeneration (AMD) wurde in den letzten Jahren zwar viel diskutiert, einen festen Platz in der Reihe der Behandlungsmoglichkeiten der AMD konnte sie bisher nicht erringen [3,4,6,[8][9][10]14]. Ursachen dafiir sind einerseits das Fehlen von Studien mit grol3eren Patientenzahlen mit eindeutiger Wirkung der Strahlentherapie auf den Verlauf der AMD, andererseits aber auch die biologische bzw.…”
Section: Introductionunclassified
“…Ein Wachstumstillstand der CNV bei AMD and der damit verbundenen gunstigen Beeinflussung des funktionellen Verlaufes wurde nach Bestrahlung der Makula beschrieben [1,2,4,7,12]. Die Narben der bestrahlten Augen wiesen eine deutlich geringere GroBe auf als die der kontralateralen Augen im Spontanverlauf [11].…”
Section: Introductionunclassified
“…A differential survival response might therefore be exploited with CNV destroyed through DNA breaks that normal tissues have time to repair before undergoing cell division. [11][12][13][14][15] Although radiation dose fractionation with multiple small treatments over many days is commonly used to reduce normal tissue complications in the treatment of malignancies, since CNV is not a true neoplasm, arguments have been made that there may be no therapeutic advantage to dose fractionation, 16 especially if the volume irradiated can be restricted to the region of macula (it is an axiom of radiotherapy that the probability of complications is proportional to the size of the target volume). In the journal this month, however, a radiotherapy trial is reported which shows no benefit in AMD.…”
mentioning
confidence: 99%
“…18 Since then a multitude of small pilot studies using standard fractions of 2-3 Gy with a total dose of 10-20 Gy have been published, some showing better maintenance of visual acuity in treated eyes, [11][12][13][14]19 while others failed to show any benefit. 15,[20][21][22] Overall, prior to the study by Hoeller et al there have been 10 randomised control trials (RCT), 15,[23][24][25][26][27][28][29][30]30,31 three nonrandomised trials 15,21,32 and eight case series each with over 100 people in the study 22,[33][34][35][36][37][38][39] (see Table 1).…”
mentioning
confidence: 99%